Scalable Fabric: Flexible Task Management - Robertson, George; Horvitz, Eric; Czerwinski, Mary; Baudisch, Patrick; Robbins, Daniel; Smith, Greg (Advanced Visual Interfaces 2004, 2004)
Our studies have shown that as displays become larger, users leave more windows open for easy multitasking. A larger number of windows, however, may increase the time that users spend arranging and switching between tasks. We present Scalable Fabric, a task management system designed to address problems with the proliferation of open windows on the PC desktop. Scalable Fabric couples window management with a flexible visual representation to provide a focus-plus-context solution to desktop complexity. Users interact with windows in a central focus region of the display in a normal manner, but when a user moves a window into the periphery, it shrinks in size, getting smaller as it nears the edge of the display. The window “minimize” action is redefined to return the window to its preferred location in the periphery, allowing windows to remain visible when not in use. Windows in the periphery may be grouped together into named tasks, and task switching is accomplished with a single mouse click. The spatial arrangement of tasks leverages human spatial memory to make task switching easier. We review the evolution of Scalable Fabric over three design iterations, including discussion of results from two user studies that were performed to compare the experience with Scalable Fabric to that of the Microsoft Windows XP TaskBar.